Pelatihan dan Pendampingan Implementasi Komunikasi Pemasaran Digital Pada UMKM di Desa Sigar Penjalin, Lombok Utara - Hartin Nur Khusnia; Muhlis Muhlis; Yulanda Trisula Sidarta Yohanes (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2022)
The COVID-19 pandemic situation forces humans to minimize physical social interaction. In this context, the media in the network becomes the choice of means of interaction and communication so that each individual can stay connected. In such a situation, everyone is required to be able to adapt, including UMKM actors. However, the skill of UMKM actors in Sigar Penjalin village in utilizing digital media as a means of marketing communication is minimal, as well as the lack of ability to manage brands. Therefore this community service program carries the theme of training and assistance in implementing digital marketing communications. This activity aims to increase the knowledge and skills of UMKM actors to optimal in utilizing digital media as a means of marketing communication and the ability to manage brands well. The results of activities to increase the expertise of UMKM actors were carried out through training and mentoring focusing on the material on social media marketing and brand management. Through the training and mentoring, participants are equipped with knowledge about social media geography, product packaging, the importance of brands for producers and consumers, brand development models, and logo design using the Canva application.